Development of Interactive Multimedia Based on Adobe Flash CS6 to Improve Learning Outcomes - Roza Humaira Handayani; Yalvema Miaz; Abna Hidayati; Alwen Bentri (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to create an interactive multimedia based on Adobe Flash CS6 application in learning in elementary school. This type of research is research and development (R&D) with the ADDIE development model, starting from the analysis and design stages. The next stage is the development stage, where data collection is done through interviews and questionnaires. Data analysis was conducted to assess the validity of interactive multimedia in three aspects, namely media, material, and language. Validators provided quantitative and qualitative feedback. Results the validity test showed a validation score of 92% from the material expert, the language validation results obtained a score of 81%, and the media validation obtained a score of 80% with a very valid category. This shows that each specification of interactive multimedia is considered valid and is included in the high category. Thus, it can be concluded that interactive multimedia is very good and feasible to use as learning media for elementary school students, so that it can be used in the learning process.